Honduras : Country Procurement Assessment Report - World Bank (Washington, DC, 2012)
The CPAR's general recommendation is based on the premise that full consolidation and integration of the existing procurement systems arrangements (regulatory and human resources) into one harmonized system, anchored on the effective implementation of the LCE, remains of paramount importance to improve public procurement in Honduras. For this to be possible and for the current reform to remain on track offering short term results, the GOH must take decisions on the following three issues: 1) Effective operation of the Oficina Normativa de Contratación y Aquisiciones (ONCAE); 2) Prompt and coordinated implementation of the program for efficiency and transparency in government procurement; and 3) Review of the government policy on the use of Project Implementing Units. Annex 1 of this CPAR provides an action plan to implement and follow up on its recommendations. This action plan was prepared jointly with the activities and products involved in the action plan of the Program of Efficiency and Transparency in Public Procurement (PET). This plan focuses on the four procurement system areas: Planning, regulation, implementation, and control.